Cognitive rehabilitation using virtual reality in subjective cognitive decline and mild cognitive impairment: a systematic review - Maggio, Maria Grazia; Maione, Raffaela; Cotelli, Maria; Bonasera, Piero; Corallo, Francesco; Pistorino, Giulia; Luca, Antonina; Marra, Angela; Quartarone, Angelo; Nicoletti, Alessandra; Calabrò, Rocco Salvatore (Frontiers in Psychology, 2025)
BackgroundMild Cognitive Impairment (MCI) and Subjective Cognitive Decline (SCD) are heterogeneous conditions that may indicate early dementia. Virtual Reality (VR) is emerging as a promising non-pharmacological tool for cognitive training. However, its effectiveness in these populations remains unclear. This systematic review examines the impact of VR-based cognitive interventions in individuals with SCD and MCI.MethodsA systematic review was conducted in accordance with PRISMA guidelines. Studies published between 2019 and 2025 investigating VR-based cognitive interventions in individuals diagnosed with SCD or MCI were identified through searches in PubMed, Scopus, Embase, and Web of Science. Eligible studies included randomized controlled trials (RCTs), experimental studies, and usability studies.ResultsNineteen studies met the inclusion criteria, including 14 RCTs, 2 usability studies, and 3 experimental studies. The majority of studies reported significant improvements in various cognitive domains, particularly memory, attention, and executive function, following VR-based interventions. Several studies also highlighted the positive impact of VR on user engagement and motivation, with high adherence and low dropout rates. However, there was considerable variability in intervention protocols, cognitive outcome measures, and participant characteristics. Most studies focused on individuals with MCI, while research on SCD populations remains limited and preliminary. Methodological quality varied, with some studies lacking adequate sample sizes or long-term follow-up.ConclusionVR-based cognitive interventions appear to be a feasible and potentially effective approach for enhancing cognitive function in individuals with MCI, with emerging evidence also supporting their use in SCD. Despite encouraging results, further high-quality, large-scale trials are needed to validate these findings, standardize intervention protocols, and explore long-term benefits.Systematic review registrationCRD42025644894.